MIN 20 Aceh Besar لترقية قدرة التلاميذ على المفردات بـ Total Physical Response وطريقة Drill and Practice مقارنة بين طريقة - Rahmah, Annisa; Ninoersy, Tarmizi; Fadhilah, Fadhilah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2022)
The tittle of this research is a “Comparison Between the Drill and Practice Method and the Total Physical Response Method to Improve Student’s Ability in Vocabulary Mastery (Experimental Study at MIN 20 Aceh Besar)”. The researcher chose this tittle because the researcher found that the students felt Arabic was a difficult subject. This is caused by the use of methods by teachers who do not vary by only taking notes and memorizing vocabulary so that it makes students bored and eventually had difficulty following the lesson. Therefore, the researcher wants to use these two methods in improving student’s vocabulary mastery skills in order to find out if there is a difference in the effect between these two methods. The research method is the experimental method. The researcher took samples from class 5.1 with 20 students for the control class and class 5.2 with 20 students for the experimental class. This study uses a question instrument consisting of pre-test and post-test with descriptive statistical data analysis techniques, paired sample t-test and independent sample t-test using the SPSS v.25 program. The results of this study using the paired sample t-test showed that the Drill and Practice method and the Total Physical Response method had an effect on increasing student’s ability in vocabulary mastery. Which the alternative hypothesis is accepted and the null hypothesis is rejected. The results of the study using the independent sample t-test showed that there was no difference in the effect between the use of the Drill and Practice method and the Total Physical Response method in vocabulary learning. Thus, the alternative hypothesis is rejected and the null hypothesis is accepted.